2011
DOI: 10.1074/jbc.m110.216200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nuclear Receptor Coactivator AIB1-Δ4 Splice Variant in the Control of Gene Transcription

Abstract: The oncogene amplified in breast cancer 1 (AIB1) is a nuclear receptor coactivator that plays a major role in the progression of various cancers. We previously identified a splice variant of AIB1 called AIB1-⌬4 that is overexpressed in breast cancer. Using mass spectrometry, we define the translation initiation of AIB1-⌬4 at Met 224 of the full-length AIB1 sequence and have raised an antibody to a peptide representing the acetylated N terminus. We show that AIB1-⌬4 is predominantly localized in the cytoplasm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…38,39 Overexpression of AIB1-∆4 is associated with increased metastatic potential of breast cancer cells. 39,40 Irrespective of this additional complexity, higher levels of AIB1 mRNA or AIB1 gene amplification in breast cancers are generally predictive of worse disease outcome, higher grade disease, shorter disease-free interval, and reduced overall survival. 13,27,41,42 AIB1 has been widely studied for its role in resistance to SERM therapy in breast cancer both preclinically and clinically.…”
Section: Aib1mentioning
confidence: 99%
“…38,39 Overexpression of AIB1-∆4 is associated with increased metastatic potential of breast cancer cells. 39,40 Irrespective of this additional complexity, higher levels of AIB1 mRNA or AIB1 gene amplification in breast cancers are generally predictive of worse disease outcome, higher grade disease, shorter disease-free interval, and reduced overall survival. 13,27,41,42 AIB1 has been widely studied for its role in resistance to SERM therapy in breast cancer both preclinically and clinically.…”
Section: Aib1mentioning
confidence: 99%
“…Alternative splicing results in the loss of exon 4, thereby shifting the start codon to exon 7 and forming a N-terminal truncated, yet functional protein, missing 224 amino acids [20,21]. As the isoform retains its nuclear receptor interacting domain, poly-Q region, and its C-terminal activation domains, the isoform can localize to estrogen response elements in the nucleus and recruits CBP/p300 to activate hormone dependent transcription [22]. Moreover, Δ4 isoform can also utilize its C-terminal activation domains, meaning that it can still co-activate many of hormone receptors and transcription factors on which it usually acts (see Sections 4 and 6).…”
Section: The Aib1δ4 Isoformmentioning
confidence: 99%
“…A more recently recognized mechanism of epigenetic regulation is the alternative splicing of mRNA transcripts, allowing for the generation of multiple unique proteins from the same message, which may have differential and even opposing functions [95,96]. For example, our lab has studied the role of the nuclear co-activator and oncogene, amplified in breast cancer 1 (AIB1), and we have identified an alternatively processed transcript of the mRNA which generates a shorter form of the protein named AIB1-Δ4 [97]. We have demonstrated an upregulation of this variant in breast cancer and have associated the alternative processing with loss of a regulatory domain, potentiating the oncogenic function of AIB1 [97].…”
Section: Epigenomic Changes During Progressionmentioning
confidence: 99%
“…For example, our lab has studied the role of the nuclear co-activator and oncogene, amplified in breast cancer 1 (AIB1), and we have identified an alternatively processed transcript of the mRNA which generates a shorter form of the protein named AIB1-Δ4 [97]. We have demonstrated an upregulation of this variant in breast cancer and have associated the alternative processing with loss of a regulatory domain, potentiating the oncogenic function of AIB1 [97]. Our lab has also shown that AIB1 is upregulated in the transition from normal breast to DCIS and maintained in the transition to invasive carcinoma [98].…”
Section: Epigenomic Changes During Progressionmentioning
confidence: 99%